The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18203/2320-6012.ijrms20182805
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of smartphone addiction and related factors among university students

Abstract: Background: The purpose of this study is to investigate the level of smartphone addiction of university students and determine the related factors.Methods: This cross-sectional study was conducted among first and third-class students of the 2016 fall semester in Eskişehir Osmangazi University with 1492 students. In this study, risk of smartphone addiction was evaluated by using Short Version of Smartphone Addiction Scale (SAS-SV). In data analysis, Mann Whitney U, Kruskal Wallis and hierarchical multi linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
(31 reference statements)
4
13
0
2
Order By: Relevance
“…The research was conducted in North Sumatra with medical students as respondents and discovered that the average age of the respondents was 19.71 years. Similarities in terms of the characteristics of the respondent's age variable can also be found in other studies, but these studies do not specifically mention the trend of respondent's age [16], [23], [27] In terms of gender characteristics, most of the respondents in this research are female. This happened because the prevalence of female students is higher than male students.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The research was conducted in North Sumatra with medical students as respondents and discovered that the average age of the respondents was 19.71 years. Similarities in terms of the characteristics of the respondent's age variable can also be found in other studies, but these studies do not specifically mention the trend of respondent's age [16], [23], [27] In terms of gender characteristics, most of the respondents in this research are female. This happened because the prevalence of female students is higher than male students.…”
Section: Discussionsupporting
confidence: 72%
“…This happened because the prevalence of female students is higher than male students. Comparable gender characteristics of respondents were also found by several types of research regarding the association between smartphone addiction and insomnia [14], [16], [23], [26], [27], [28], [29]. The percentage difference between female and male respondents in these studies varied in the range of 2-53%.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nesse contexto, a literatura relata a existência de fatores motivacionais, os quais podem ser intrínsecos e extrínsecos (RYAN;DECI, 2000). A socialização e diversão são exemplos de fatores extrínsecos que podem favorecer com que a pessoa fique mais tempo nos smartphones e em CS (ZENCIRCI et al, 2018), porém os mesmos fatores podem incentivar a pessoa a realizar outro comportamento, como foi identificado na fala dos escolares. Assim, saber como utilizar a motivação para a melhoria da saúde é interessante, uma vez que ela possui influência nas ações dos indivíduos (RYAN; DECI, 2000).…”
Section: Resultsunclassified
“…Niro et al (2020) reported that 48% of 126 samples spent duration more than 12 hours using gadgets, and it, mostly, was for playing games (29,5) and watching videos (32,8%). Zencirci et al (2018) also proved that social contacts and entertaining applications/content increase students' addiction to the gadget. Therefore, it is not surprising that people often used their gadgets to access entertaining applications and social simulation games like the Animal Crossing series or Minecraft.…”
Section: Abstrakmentioning
confidence: 88%